(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2024)
Abstract: The fishing industry in Sri Lanka generates significant waste, presenting an opportunity to convert it into a sustainable energy source. This research investigates the production of biodiesel from fish waste, specifically fish oil, as an alternative fuel to reduce reliance on fossil fuels and improve waste management in the fish market. Fish waste, including non-edible parts such as fish heads, tails, fins, and internal organs, was collected from a local fish market and subjected to an extraction process using wet boiling. The extracted fish oil was then converted into biodiesel through a transesterification reaction with methanol in the presence of potassium hydroxide (KOH) as a catalyst. Two optimization experiments were conducted to determine the best methanol concentration (15%, 20%, and 25%) and KOH concentration (1g, 2g, and 3g). The results showed that the highest biodiesel yield was obtained using 20% methanol (producing 10.71g of biodiesel) and 1g of KOH as a catalyst, yielding a biodiesel production of 8.66g for 15% methanol and 6.89g for 25% methanol. The biodiesel produced exhibited promising fuel properties, with a flashpoint of 127.5°C, a calorific value of 39.248 MJ/kg, kinematic viscosity of 4.4107 mm²/s, and density of 0.8766 g/cm³, all of which were within the acceptable limits set by ASTM standards. Additionally, the FFA content of the extracted fish oil was initially 7%, which was reduced through a saponification process, making the oil suitable for biodiesel production. The study estimated that approximately 237 metric tons of biodiesel could be produced per month from the fish waste in Sri Lanka, based on the average monthly fish waste generated (50% of total fish production). The biodiesel production from fish oil thus holds significant potential as both a renewable energy source and a sustainable waste management solution, reducing the reliance on fossil fuels and addressing environmental challenges associated with waste disposal in the fishing industry.